Back Cover: Orbital Engineering: Photoactivation of an Organofunctionalized Polyoxotungstate (Chem. Eur. J. 1/2017). Issue 1 (5th December 2016) - Cameron, Jamie M.; Fujimoto, Satomi; Kastner, Katharina; Wei, Rong‐Jia; Robinson, David; Sans, Victor; Newton, Graham N.; Oshio, H. Hiroki
Abstract : Simple organic functionalization was shown to be a cost‐effective and durable approach to the visible‐light photoactivation of polyoxometalates (POMs). A new organic–inorganic hybrid polyoxometalate showed greatly enhanced photocatalytic activity in the visible region compared with analogous, non‐hybridized POM clusters. The new hybrid POM takes center stage in the cover art, illuminated by the sun of (possibly) a new dawn in molecular metal oxide photochemistry. More information can be found in the Communication by G. N. Newton and H. H. Oshio et al. onpage 47 ff.